2022
DOI: 10.3389/fimmu.2022.869286
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD73+ Double-Negative T Cells and Elevated Level of Soluble CD73 Correlated With and Predicted Poor Immune Reconstitution in HIV-Infected Patients After Antiretroviral Therapy

Abstract: Although extensive use of antiretroviral therapy (ART) has made great progress in controlling HIV replication and improving CD4+ T cell recovery, the immune reconstitution remained insufficient in some patients, who were defined as poor immunological responders (PIRs). These PIRs were at a high risk of AIDS-related and non-AIDS complications, resulting in higher morbidity and mortality rate. Thus, it is a major challenge and urgently needed to distinguish PIRs early and improve their immune function in time. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…In line with previous studies, we also found that DNT cells increased with disease progression of HIV infection ( Figure S1A ) ( 24 ). To further investigate the potential role of Foxp3 in DNT cells during HIV infection, we performed intracellular flow cytometric analysis of Foxp3 in DNT cells.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In line with previous studies, we also found that DNT cells increased with disease progression of HIV infection ( Figure S1A ) ( 24 ). To further investigate the potential role of Foxp3 in DNT cells during HIV infection, we performed intracellular flow cytometric analysis of Foxp3 in DNT cells.…”
Section: Resultssupporting
confidence: 93%
“…CD25 rendered Treg cells able to rapidly sense IL-2 produced by self-reactive conventional T cells early in the immune response and compete for growth factors ( 27 ). CD39 was an ectoenzyme that converted ATP into adenosine in tandem with CD73, which was reported to involve in the immune regulation mediated by DNT cells in our recent study ( 24 ). Additionally, GITR triggering in vivo effectively increased the absolute number of cells through enhanced proliferation ( 36 ), which was in line with high levels of Ki-67 in Foxp3 + DNT cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is important to note that in recent years increasing circumstantial evidence has been gathered, independently suggesting a critical role for either hypoxia [53][54][55][56][57] , CD73 expression [60][61][62] or adenosine signaling [63][64][65][66][67] in HIV infections. Our data now implies a direct, causal connection that links the hypoxic regulation and adenosineproducing enzymatic activity of CD73 to the establishment and persistence of viral reservoirs.…”
Section: Discussionmentioning
confidence: 99%